Implementasi Model Blended Learning Berbasis CAT Bagi Penggerak Literasi Digital Pada Peserta Bimbel CPNS PT Javas Anugerah Perkasa - Selviani, Diah; Maryani, Desy; Rachayu , Imma; Elfianty , Lena; Nurhanifah (Jurnal Kewirausahaan dan Bisnis, 2021)
Increasing digital literacy has become an urgent need in the current digitalization era. This article aims to explain the implementation of a Computer Assisted Testing (CAT)-based blended learning model as a strategy to increase digital literacy in Study Guidance participants for Prospective Civil Servants (CPNS) at PT Javas Anugerah Perkasa. This study uses a community service approach involving instructors and CPNS Bimbel participants as research subjects. The blended learning model is a combination of online and face-to-face learning which aims to optimize the learning process. In implementing this model, CAT is used as an evaluation tool to measure participants' digital literacy levels. This article explains how the blended learning model with CAT can provide an interactive, adaptive learning experience and enable participants to develop their digital literacy skills. The results of this study indicate that the implementation of the CAT-based blended learning model was able to increase the digital literacy of PT Javas Anugerah Perkasa Civil Servants Bimbel Bimbel participants. Participants are able to develop an understanding of the basic concepts of digital literacy, increase their ability to use digital technology effectively, and are able to use information wisely in the context of their work as prospective civil servants. This article contributes to the development of effective learning strategies to improve digital literacy in non-formal education contexts.